Polyacrylamide gel electrophoresis - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1988)
Polyacrylamide gel electrophoresis is used to analyze DNA fragments of less than 1 kilobase in length
Copy available in DVD format
Narrated by William Lowry
Keywords: Polyacrylamide gel electrophoresis